Memahami Pentingnya Dukungan Sosial Dalam mencapai Penerimaan Diri Pada Dewasa Melajang - Muthami’mah, Ervia Nur; Suroso, Suroso; Rista, Karolin (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
Marriage is still the cornerstone of today's culture because marriage is an aspect of culture that is passed down from generation to generation with the aim of giving birth to future generations. This study aims to determine whether there is a relationship between social support and self-acceptance in single adults. Subject The data analysis technique used in this study was non-parametric using the Spearman-Rho correlation analysis method using the computer program SPSS version 16.00 (Statistical Product and Service Solution) for Windows. In this research, the population that is the focus is the Indorunners Surabaya community, which consists of individuals with the criteria of men and women aged 25 to 40 years who have never or have never had a marriage relationship. The results of the study show that there is a positive and significant relationship between social support and self-acceptance. That is, the higher the social support received, the higher the self-acceptance of single adults. Individuals with low self-acceptance tend to experience stress and feel unaccepted and lack self-confidence. The imbalance between the pressure faced and the inability to deal with it can affect individual self-acceptancePernikahan masih tetap menjadi landasan budaya saat ini karena pernikahan merupakan salah satu aspek budaya yang diturunkan dari generasi ke generasi dengan tujuan untuk melahirkan generasi di masa depan. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara dukungan sosial dengan penerimaan diri pada dewasa yang masih melajang. Subjek Teknik analisis data yang digunakan pada penelitian ini adalah secara non-parametrik dengan metode analisis korelasi Spearman-Rho menggunakan program komputer SPSS versi 16.00 (Statistical Product and Service Solution) for Windows. Penelitian ini populasi yang menjadi fokus adalah komunitas Indorunners Surabaya yang terdiri dari individu dengan kriteria laki-laki dan perempuan usia 25 sampai 40 tahun belum pernah atau tidak pernah melakukan hubungan pernikahan. Hasil penelitian ada hubungan positif dan signifikan antara dukungan sosial dengan pemerimaan diri. Artinya, semakin tinggi dukungan sosial yang diterima maka semakin tinggi pemerimaan diri pada dewasa yang masih melajang. Individu dengan penerimaan diri rendah cenderung mengalami stres dan merasa tidak diterima serta kurang percaya diri. Ketidakseimbangan antara tekanan yang dihadapi dan ketidakmampuan menghadapinya dapat memengaruhi penerimaan diri individu.